The Development of Biru Kersik Coast Tourism in Marangkayu, Sub-District of Kutai Kartanegara (A Review of Sharia National Council-Indonesian Ulema Council Fatwa Number 108/DSN-MUI/X/2016 about Tourist Guidelines Based on Sharia Principles) - Darmawati Darmawati; Birusman Nuryadin (Institut Agama Islam Negeri (IAIN) Curup, 2022)
Purpose: The aim of this study is to knowing the concept of sharia tourism services and facilities at Biru Kersik Coast in Marangkayu through reviewing the DSN-MUI Fatwa number 108/DSN-MUI/X/2016, and how its development accompanied by supporting and inhibiting factors.Design/Method/Approach: This study uses a descriptive analytical approach, to reveal a problem and the situation as it is at Biru Kersik Coast. It intensively implemented a qualitative approach to obtain information. The data collection techniques used in this study were interviews, observation, and documentation. The selected informants who are directly related to the Biru Kersik Coast Tourist.Findings: The concept of Biru Kersik Coast tourism services and facilities in Marangkayu are worthy as a tourist destination because of the accessibility and facilities provided. A sharia review of the Biru Kersik Coast tourist attraction in Marangkayu shows that the Coast has not yet fully adopted tourism services and facilities according to sharia principles because there are several aspects that have not been fulfilled such as not being separated between male and female visitors. Meanwhile, aspects that are in accordance with sharia principles are the presence of facilities and infrastructure for worship, bathrooms and places for ablution, halal food and drinks, and does not provide access to pornography and immoral acts as well as entertainment that leads to polytheism and immorality.Originality/Values: The main contribution in this study is to determine the suitability between the tourist destinations of Samarinda Biru Kersik Coast with the DSN-MUI, so as to create a tourism environment that is in accordance with sharia. Therefore, the atmosphere in tourism will provide a safe environment, without fear of things that are forbidden by the sharia.